Early midtrimester serum insulin-like factors and cervical length to predict preterm delivery - Jae Eun Shin; Jong Chul Shin; Sa Jin Kim; Young Lee; In Yang Park; Seungok Lee (Elsevier, 2016)
Objective: To investigate which ultrasound findings or serum biomarkers, including insulin-like growth factor 1 (IGF-1) and insulin-like growth factor binding protein 1 and 3 (IGFBP-1 and IGFBP-3, respectively), in the first and early second trimesters are the best predictors for preterm delivery. Materials and Methods: This was a case-control study conducted between March 2011 and March 2013 with women presenting for routine antenatal care at 11-18 weeks. We collected serum samples from pregnant women and stored them at −80°C. All patients underwent cervical length (CL) measurement at 18-21 weeks. We retrieved frozen samples for analysis from women with subsequent preterm and term delivery. Prediction models were developed using multivariate stepwise logistic regression. Receiver-operating characteristics curves were used to determine the most useful cutoff point. Results: Of the 72 women recruited, 24 women underwent spontaneous preterm delivery, and 48 women with term delivery were randomly selected as the control group, in a 1:2 ratio. The maternal serum concentration of IGFBP-3 and CL were significantly associated with preterm birth. Conclusion: Among the various known ultrasound findings and serum biomarkers in the early midtrimester, only CL and IGFBP-3 are independent predictors for preterm delivery in asymptomatic women.